Mawlana Mawdudi and political Islam : authority and the Islamic state - Jackson, Roy, 1962- (London ; New York : Routledge, 2011)
Mawlana Mawdudi was one of the most influential and important Islamic thinkers of the 20th century. His brand of political Islam has won widespread acceptance in South and South East Asia as well as the Middle East. This text critically engages and assesses his career and legacy.
The life and times of Mawdudi -- A noble lineage. 1903-1919 -- "A hidden power within me", 1920-1930 -- Crisis of the spirit, 1930-1939 -- The birth of a new party, 1940-1947 -- The Pakistan years, 1947-1979 -- Mawdudi and political Islam -- The need for "intellectual independence" -- The Salafiyyah -- Mawdudi's paradigms: the four sources of his Islamic constitution -- Theo-democracy (or divine government?) -- Jihad and the permanent revolution -- Mawdudi's legacy.
Includes bibliographical references (pages 190-196) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Maudoodi, Syed Abul ʻAla, -- 1903-1979.; Maudoodi, Syed Abul ʻAla, -- 1903-1979 -- Political and social views; Maudoodi, Syed Abul ʻAla, -- 1903-1979.; Muslim scholars -- India -- Biography; Muslim scholars -- Pakistan -- Biography; Salafīyah -- History; India; Pakistan; Electronic books